Interpreting vaccine-associated survival differences in immune checkpoint inhibitor therapy - René Karadakic; Nancy L. Keating; Michael L. Barnett (Proceedings of the National Academy of Sciences, 2026)
Recent studies proposed that SARS-CoV-2 mRNA vaccination may sensitize tumors to immune checkpoint inhibitor (ICI) therapy through immune modulation. Using 100% national Medicare fee-for-service claims data, we evaluated whether survival differences among vaccinated patients receiving ICIs were specific to mRNA vaccines. Among 121,676 beneficiaries initiating systemic anticancer therapy, including 10,824 initiating ICIs, vaccination near treatment initiation was associated with lower mortality across mRNA COVID-19, adenoviral COVID-19, and influenza vaccines. We found that survival associations and formal vaccine–ICI interaction effects were similar across vaccine platforms. These findings suggest that currently available population-level survival data do not isolate an mRNA-specific tumor-sensitization mechanism.